PENGARUH PEMAHAMAN AGAMA ISLAM DAN DOMINASI BUDAYA SEKULER TERHADAP KEPATUHAN BERIBADAH DAN PERILAKU INDIVIDUALISTIK MAHASISWA DI UIN AMBON - Muhammad Ali Farhan Marasabessy (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to analyze the influence of Islamic understanding and the dominance of secular culture on students’ worship compliance and individualistic behavior. The research employed a quantitative approach with a survey design and multiple linear regression techniques. The sample consisted of students selected purposively. The findings reveal that Islamic understanding has a significant and positive effect on worship compliance, as well as contributing to reducing individualistic tendencies. Conversely, the dominance of secular culture negatively affects worship compliance while increasing individualism. These results highlight the importance of integrating Islamic values within higher education to foster both religious and social character among students. The implications of this research encourage the strengthening of value-based religious education and the adoption of a holistic approach in nurturing students’ spiritual and intellectual balance